NPR-1 Modulates Plasticity in C. elegans Stress-Induced Sleep - Soto, Rony (iScience, 2019)
Sleep is beneficial yet antagonistic to critical functions such as foraging and escape, and we aim to understand how these competing drives are functionally integrated. C. elegans, which lives in reduced oxygen environments, engages in developmentally timed sleep (DTS) during larval stage transitions and engages in stress-induced sleep (SIS) during recovery from damaging conditions. Although DTS and SIS use distinct mechanisms to coordinate multiple sleep-associated behaviors, we show that movement quiescence in these sleep states is similarly integrated with the competing drive to avoid oxygen. Furthermore, by manipulating oxygen to deprive animals of SIS, we observe sleep rebound in a wild C. elegans isolate, indicating that sleep debt accrues during oxygen-induced SIS deprivation. Our work suggests that multiple sleep states adopt a common, highly plastic effector of movement quiescence that is suppressed by aversive stimuli and responsive to homeostatic sleep pressure, providing a limited window of opportunity for escape.